2019
DOI: 10.3390/su12010112
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Urban Heat Island Intensity According to Urban Area Change in Asian Mega Cities

Abstract: Urban heat island (UHI) is a phenomenon that occurs in cities worldwide. Therefore, there is an increasing need for studies on the changes in UHI intensity and long-term trends based on macroscopic characteristics related to urbanization. In this study, changes in seasonal UHI intensity based on urban area were analyzed for eight Asian mega cities from 1992-2012. The results indicate that the change in pattern of UHI intensity varies for different cities and seasons. UHI intensity increased as the urban area s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 37 publications
2
38
0
1
Order By: Relevance
“…This is contrary to the observation in Figure 14d-f in which the UHI peak occurred in the evening as a result of clear sky for the rest of the days. Figure 15 shows the hourly average of UHI intensity over six (6) days. Overall, the hourly average of UHII ranged between 1.0 °C and 4.0 °C, which was equal between the urban and rural areas.…”
Section: Temporal Analysis Of Uhi Intensity (Uhii)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is contrary to the observation in Figure 14d-f in which the UHI peak occurred in the evening as a result of clear sky for the rest of the days. Figure 15 shows the hourly average of UHI intensity over six (6) days. Overall, the hourly average of UHII ranged between 1.0 °C and 4.0 °C, which was equal between the urban and rural areas.…”
Section: Temporal Analysis Of Uhi Intensity (Uhii)mentioning
confidence: 99%
“…All calculated values of UHII are positive values, indicating that the high temperature recorded at Kampung Baru contributed to the UHI phenomenon. Figure 15 shows the hourly average of UHI intensity over six (6) days. Overall, the hourly average of UHII ranged between 1.0 • C and 4.0 • C, which was equal between the urban and rural areas.…”
Section: Temporal Analysis Of Uhi Intensity (Uhii)mentioning
confidence: 99%
See 1 more Smart Citation
“…CHELSA has a global coverage, and it contains monthly mean temperature and precipitation for the time period 1979-2013 at a 30-arc sec-spatial resolution. Recently, [58] employed the CHELSA dataset, validated with independent station data provided by the Global Historical Climatology Network (https://www.ncdc.noaa.gov/dataaccess/land-based-station-data/land-based-datasets/ global-historical-climatology-network-ghcn), to analyze the trend in urban heat island intensity from 1992 to 2012 for eight megacities in Asia. The study revealed the ability of the dataset to capture the characteristics of the urban heat island and a good match between the increase in air temperature and urban sprawl.…”
Section: Gridded Datasetsmentioning
confidence: 99%
“…The change in the local climate as a result of a distinguishing land-use pattern in an urban area is often referred as the urban heat island (UHI) effect. The UHI effect is recognized as being caused by a reduction in the latent heat flux and an increase in sensible heat in urban areas as vegetated and evaporating soil surfaces are replaced by pavement and building materials with relatively impervious and low albedo [37][38][39][40]. Consequently, cities are exposed to climate change from greenhouse gas-induced radiative forcing, and localized effects from urbanization such as the urban heat island.…”
Section: Introductionmentioning
confidence: 99%